2017
DOI: 10.3389/fnmol.2017.00069
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Expression Analysis in a Mouse Model of Tauopathy Identifies MECP2 as a Possible Regulator of Tau Pathology

Abstract: Increasing evidence suggests that hyperphosphorylation and aggregation of microtubule-associated protein tau (MAPT or tau) correlates with the development of cognitive impairment in Alzheimer’s disease (AD) and related tauopathies. While numerous attempts have been made to model AD-relevant tau pathology in various animal models, there has been very limited success for these models to fully recapitulate the progression of disease as seen in human tauopathies. Here, we performed whole genome gene expression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 50 publications
1
27
1
Order By: Relevance
“…Here, we found that tau overexpression led to the loss of miR‐132, while miR‐132 deficiency in mice led to increased tau expression, phosphorylation, and aggregation. Moreover, in the hTau mouse brain, the MeCP2 level is increased, and MeCP2 can regulate tau expression and phosphorylation and thus contribute to tauopathy in AD (Maphis et al, ). These studies strongly suggest a vicious cycle of miR‐132‐tau or tau‐miR‐132‐MeCP2‐tau abnormalities in the tauopathies.…”
mentioning
confidence: 99%
“…Here, we found that tau overexpression led to the loss of miR‐132, while miR‐132 deficiency in mice led to increased tau expression, phosphorylation, and aggregation. Moreover, in the hTau mouse brain, the MeCP2 level is increased, and MeCP2 can regulate tau expression and phosphorylation and thus contribute to tauopathy in AD (Maphis et al, ). These studies strongly suggest a vicious cycle of miR‐132‐tau or tau‐miR‐132‐MeCP2‐tau abnormalities in the tauopathies.…”
mentioning
confidence: 99%
“…The reduction of CERS1 protein in the Atxn2-CAG100-KIN mouse was accompanied by a decrease of Cers1 mRNA and correlated with the mild deficiency of many ceramide species. CERS1 inactivity leads to preferential degeneration of cerebellar Purkinje neurons, and Cers1 mRNA downregulation was reported in tauopathies [142], so a pathogenic role of CERS1 deficiency in SCA2 is likely. Similarly, a deficiency of Smpd3 encoding nSMase2 as detected in the KIN nervous tissue was reported to cause TDP-43 neurotoxicity and tauopathy, while Ataxin-2 depletion protects against TDP-43 aggregation and tauopathies, so this dysregulation appears to be another pathogenic event with SCA2-typical features.…”
Section: Discussionmentioning
confidence: 99%
“…115,116 Recent studies on epigenetic modifications in AD animal models with Aβ and tau-related pathologies showed upregulated MeCP2 levels in the hippocampus. 117,118 Although an increased level of phosphorylated MeCP2 was simultaneously observed in these AD animals, the phosphorylated site was reported to be at Ser80, whereas pSer421 remained unchanged. 118 Hence, it is possible that Aβ and tau-related pathology work in concert to suppress Bdnf expression, which disrupts normal synaptic functions, resulting in synaptic impairment and neuronal loss.…”
Section: Neurochemical Processesmentioning
confidence: 90%